Breast Cancer: IL1R2 Blockade Suppresses Breast Tumorigenesis and Progression by Impairing USP15‐Dependent BMI1 Stability (Adv. Sci. 1/2020). Issue 1 (8th January 2020) - Zhang, Lixing; Qiang, Jiankun; Yang, Xiaoli; Wang, Dong; Rehman, Adeel ur; He, Xueyan; Chen, Weilong; Sheng, Dandan; Zhou, Lei; Jiang, Yi‐zhou; Li, Tao; Du, Ying; et al.
Abstract : In article 1901728, Suling Liu and co‐workers report that the "decoy receptor" IL‐1 receptor 2 (IL1R2) is highly expressed on the most tumorigenic intermediate‐state breast tumor initiation cells (BTICs), which fall in between the epithelial‐like state and mesenchymal‐like state. IL‐1β in the tumor microenvironment activates the IL1R2 signaling pathway and then increases intermediate‐state BTIC self‐renewal and tumor progression, which can be specifically blocked by IL1R2 neutralizing antibody.